University Coaching Experience and Academic Performance - Rodríguez Fuentes, Antonio; Navarro Rincón, Antonia; Carrillo-López, María José; Isla Navarro, Laura (MDPI, 2023)
The university education process has changed, involving new roles for the student body and the teaching staff. While teachers train for these new functions, it is not the case for students who are neither prepared for group work nor to construct their learning strategy. Coaching can be an essential success factor here. Having been applied in other educational areas, such as educational coaching, and in other non-educational ones, such as sports or business coaching, this original work proposes to evaluate the effectiveness of a university coaching programme in academic performance. Therefore, the aim is to measure the impact of an independent variable, a hybrid coaching programme, on a dependent variable, university academic performance. Trainee teachers in the Melilla Campus of the University of Granada in Spain participated in this coaching programme. The research followed a quasi-experimental design with experimental and control groups (n = 70 students, and n = 69 students, respectively) with repeated initial and final evaluation measurements (pre-treatment and post-treatment). The professor and the students conducted academic performance evaluations. The performance of the experimental group was increased compared to that of the control one, considering significant differences concerning the starting point both in the average marks provided by the professor for the practices and in those of the students. Other works about coaching have highlighted its advantages, although they are not exclusively focused on the academic area like this study. This study has limitations and needs further research. However, it concludes that the coaching applied to trainee teachers enhances their performance in practical group tasks.
Keywords: Enseñanza superior - Rendimiento; Higher education; University coaching; Academic performance; Intervention programme; Quasi-experimental study